Agricultural research for resource-poor farmers part I: transfer-of-technology and farming systems research - Chambers, Robert; Jiggins, Janice; East-West Environment and Policy Institute; Southeast Asian Universities Agroecosystem Network; SUAN Information Support Service; Ford Foundation; East-West Center (1987)
The greatest challenge now facing agricultural science is not how to increase production overall but how to enable resource-poor farmers to produce more. The transfer-of-technology (TOT) model of agricultural research is part of the normal professionalism of agricultural scientists. In this model, scientists largely determine research priorities, develop technologies in controlled conditions, and then hand them over to agricultural extension to transfer to farmers. Although strong structures and incentives sustain this normal professionalism, many now recognize the challenge of its bad fit with the needs and conditions of hundreds of millions of resource-poor farm (RPF) families. In response to this problem, the TOT model has been adapted and extended through multi-disciplinary farming systems research (FSR) and on-farm trials. These responses retain power in the hands of scientists. Information is obtained from farmers and processed and analysed in order to identify what might be good for them. A missing element is methods to encourage and enable resource-poor farmers themselves to meet and work out what they need and want.
Summary -- The problem -- Normal professionalism and the transfer of technology model -- TOT and resource-poor farmers -- Historical explanations for non-adoption and research responses -- TOT adapted: farming systems research -- Closing the circle: whose priorities.
Photocopy.
This document has been provided by EAPI as part of its SUAN Information Support Service. The goal of this service is to make current literature relating to human ecology and agroecosystems research available to scientists participating in the Southeast Asian Universities Agroecosystem Network. Partial funding for this service is provided by a Ford Foundation grant to the East-West Center.
Includes bibliographical references (pages 51-52)
Keywords: Agriculture -- Research; Agriculture -- Technology transfer; Farming system -- Research